The Signatures of Tectonics and Glacial Isostatic Adjustment revealed by the Strain Rate in Europe - A. M. Marotta; R. Sabadini (Geophysical Journal International, 2004)
Tectonics and glacial isostatic adjustment (GIA) are simultaneously taken into account in order to quantitatively define their role in crustal deformation in Europe. A spherical finite-element model, based on the thin viscous shell approach and suitable for predicting tectonic deformation, and a spherical stratified viscoelastic Earth model, based on the normal mode approach to quantifying the effects of GIA, are used to predict intraplate deformation in Europe. Model predictions are compared with the geodetic strain rate obtained from ITRF2000 velocity solutions. Our results confirm that both geophysical processes influence intraplate deformation in Europe, with tectonics playing the leading role south of Potsdam and GIA being the only mechanism north of Onsala. Both geophysical processes affect the deformation at intermediate latitudes, where the contributions to the deformation coming from tectonics and GIA are of the same magnitude and the combined tectonic plus GIA model succeeds in reproducing the eigendirections of the local predominantly SSW-NNE directed compression. The stiffening in the East European Platform is crucial for shielding the northeastern regions from the compressional effects of Africa-Eurasia convergence and to allow SE-NW directed extension in Fennoscandia driven by GIA.